Rehabilitation of the Knowledge of Revelation - Abdul Karim Abdullah (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2021)
Muslims rose to prominence by following revelation. They faded by following tradition. For tradition is a reflection of revelation. How did tradition eclipse revelation? Tradition began to contend with revelation for attention. First, the tradition cast doubt on the ability of reason to “explain” revelation. To enhance its prestige, tradition presented itself as “equal” to revelation. As a result of the inclusion of tradition in revelation, the meaning of “revelation” changed. Revelation was no longer restricted to the word of God; it would in addition encompass the reports of men. This had an effect on the Muslim civilization. For in the longer term, tradition did not merely “supplement” revelation. It went on to “judge,” replace and even abrogate parts of revelation. Traditions – the words of persons – replaced the words of God. Thus, renewal requires rescuing revelation from weak traditions. This entails the assistance of reason, which was similarly sidelined by tradition. People were expected to follow tradition even against reason. Hence, renewal requires the affirmation of the pre-eminence of revelation in relation to reason and tradition. Tradition, for its part, requires being consigned to its role as the actualization of revelation in practice rather than its “judge” or “abrogator.”